2001
DOI: 10.1128/mcb.21.18.6122-6131.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Hyperactivity of Human Progesterone Receptors Is Coupled to Their Ligand-Dependent Down-Regulation by Mitogen-Activated Protein Kinase-Dependent Phosphorylation of Serine 294

Abstract: Breast cancers often exhibit elevated expression of tyrosine kinase growth factor receptors; these pathways influence breast cancer cell growth in part by targeting steroid hormone receptors, including progesterone receptors (PR). To mimic activation of molecules downstream of growth factor-initiated signaling pathways, we overexpressed mitogen-activated protein kinase (MAPK; also known as extracellular signal-regulated kinase) kinase kinase 1 (MEKK1) in T47D human breast cancer cells expressing the B isoform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
176
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(184 citation statements)
references
References 52 publications
(75 reference statements)
5
176
3
Order By: Relevance
“…In these cell line models, progestins (10nM R5020) typically stimulated PRE-luciferase expression 10-20-fold above vehicle-treated controls, while EGF alone (30ng/ml) was without significant effect. In contrast to our previous reports using transiently expressed constitutively activated protein kinases (16,17), the combination of EGF and R5020 (simultaneously delivered) produced a modest increase in PR transcriptional activity relative to R5020 alone, but this did not reach statistical significance. The same treatments were without effect in control experiments using T47D-Y PR-null cells (not shown).…”
Section: Simultaneous Exposure To Egf and Progestin Does Not Alter Prcontrasting
confidence: 99%
See 4 more Smart Citations
“…In these cell line models, progestins (10nM R5020) typically stimulated PRE-luciferase expression 10-20-fold above vehicle-treated controls, while EGF alone (30ng/ml) was without significant effect. In contrast to our previous reports using transiently expressed constitutively activated protein kinases (16,17), the combination of EGF and R5020 (simultaneously delivered) produced a modest increase in PR transcriptional activity relative to R5020 alone, but this did not reach statistical significance. The same treatments were without effect in control experiments using T47D-Y PR-null cells (not shown).…”
Section: Simultaneous Exposure To Egf and Progestin Does Not Alter Prcontrasting
confidence: 99%
“…Western blotting using phospho-specific antibodies indicated that EGF stimulation of T47D cells induces phosphorylation of PR Ser294 at 5-10 min, similar to that induced by R5020 at early time points (15,16). Both agents are known to activate MAPKs within 5-15 minutes (25,26).…”
Section: Egf Induces Pr Nuclear Association and Pre Bindingmentioning
confidence: 84%
See 3 more Smart Citations